From a Urinalysis Strategy to an Evaluated Urine Protein Expert System - Ivandic, M.; Ogurol, Y.; Hofmann, W.; Guder, W. G. (Methods of Information in Medicine, 2000)
Urine single protein analysis has developed into a routine method for the screening and monitoring of kidney diseases. In order to support clinical decision making by an interpretative report, a urine protein expert system (UPES) has been developed.Based on a database containing more than 500 excretion patterns, a modular knowledge base was extracted in production rules and implemented in a modern expert system shell. The resulting interpretation system has been thoroughly verified and validated. After the need of interpretation of the complex findings had been documented in a survey, its usability in routine and its knowledge representation was evaluated in 11 hospitals. A user conference confirmed a high quality level of the reports proposed by UPES. It revealed that the problem of automatic data transfer as well as the common definition of diagnostic terms by laboratorians and clinicians play a crucial role for the use of knowledge-based systems in laboratory medicine.
Keywords: Urine Protein; Evaluation; Knowledge-based System; Expert System; Decision Support